The effects of sex pheromone on female attractiveness and its role in maintaining color polymorphism in Arctia plantaginis - Selenius, Eetu (2021)
Natural and sexual selection can cause opposing selection pressures, which might help explain the maintenance of color polymorphism. It is a particularly puzzling phenomenon in aposematic species, such as the wood tiger moth (Arctia plantaginis), who should face strong selection for monomorphism. Wood tiger moth males in Finnish populations maintain two color morphs: white and yellow. The coloration is determined by one locus two allele mode of inheritance with a dominant allele for white (W) and a recessive allele for yellow coloration (y). While females also carry this gene, they do not express it phenotypically. I examined the role of sexual selection in maintaining color polymorphism by studying female attractiveness and its correlation with the total amount and the amounts of the compounds of female sex pheromone used to attract potential mates. Homozygous yellow females and heterozygous females attracted significantly more males in total than homozygous white females. The absolute amount of sex pheromone did not affect female attractiveness, but the relative amount of a minor compound had a positive correlation with attractiveness. The results also suggest that this correlation differs between female genotypes, despite them having similar amounts of all pheromone compounds. These results suggest that sexual selection has a role in maintaining color polymorphism in the wood tiger moth. The advantage gained by females carrying one or two yellow alleles may be balanced by other selective forces.